A survey of patterns for Service-Oriented Architectures. (9th May 2006) - Zdun, Uwe; Hentrich, Carsten; Van Der Aalst, Wil M.P.
Service-Oriented Architectures (SOA) are a promising means to integrate heterogeneous systems, but virtually no technology-neutral approach to holistically understand SOAs exists. We tackle this problem by introducing a survey of technology-independent patterns that are relevant for SOAs, and are working towards a formalised pattern-based reference architecture model to describe SOA concepts.